Children With Autism Spectrum Disorder Can Attribute False Beliefs in a Spontaneous-Response Preferential-Looking Task - Glenwright, Melanie; Scott, Rose M.; Bilevicius, Elena; Pronovost, Megan; Hanlon-Dearman, Ana (Frontiers in Communication, 2021)
An established body of literature indicates that children with autism spectrum disorder (ASD) have difficulty understanding figurative language due to a deficit in theory of mind, or the ability to consider the beliefs of other people. Children with ASD tend to similarly fail traditional theory of mind tasks which assess their ability to represent false beliefs. Our claim is, however, is that these tasks involve cognitive processing demands that might mask false belief understanding because they require elicited or verbal responses. We examined whether children with ASD demonstrate false-belief understanding when tested with a spontaneous-response false belief task which measures children’s eye gaze durations. The two child participant groups were composed of 20 males with ASD (aged 3 to 9 years) and 20 typically developing males (aged 2 to 5 years) who were individually matched according to verbal mental age. Children with ASD and typically developing children listened to a change-of-location story accompanied by a book with matching and non-matching pictures. The final page showed the character searching for her object in a location that was either consistent or inconsistent with her belief. Both groups of children looked reliably longer at the belief-consistent picture, regardless of whether the character’s belief was true or false, though children with ASD were slower to do so. We suggest that a spontaneous response assessment technique can potentially reveal figurative language comprehension in children with ASD in future research.